THE BIOCHEMICAL MECHANISMS OF AGING: UNDERSTANDING THE PATHWAYS TO SENESCENCE - Juraev Mukhammadnazar; Gafurova Dildora (Modern American Journals, 2025)
Aging is a complex biological process characterized by a gradual decline in physiological function, increased vulnerability to diseases, and ultimately, death. This process is influenced by genetic, environmental, and lifestyle factors. At its core, aging involves a series of biochemical mechanisms that affect cellular and molecular structures. Understanding these mechanisms provides insights into potential interventions that could promote healthy aging and extend lifespan.
Keywords: Aging, reactive oxygen species (ROS), Mitochondrial Dysfunction, autophagy, Histone Modifications